"Pregnancy Brain": A Review of Cognitive Changes in Pregnancy and Postpartum. Issue 3 (March 2019) - Brown, Elinor; Schaffir, Jonathan
Abstract : Importance: The idea that pregnant women suffer from deficits in memory is widespread but poorly documented in obstetrical literature. Objective: To review available psychology literature on the subject of cognitive changes in pregnancy in order to guide the prenatal care provider on how to counsel pregnant women. Evidence Acquisition: An extensive review of PubMed and PsycINFO databases was conducted to gather and analyze relevant studies on cognitive changes in pregnancy. Results: A large body of literature examining basic science and animal studies support the effects of pregnancy hormones in remodeling brain architecture and neural function. However, studies in humans are hampered by small sizes, heterogeneous methodology, and varying definitions of memory. Nevertheless, the consensus among researchers is that pregnancy does confer deficits in working memory relative to nonpregnant controls. Conclusions and Relevance: Cognitive effects of pregnancy are likely small, and the impact on daily life is debatable. Further research is needed to determine whether these effects may confer an advantage to parous women comparable to that seen in lower mammals. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After reading this article, readers should be better able to explain prior research into the incidence of brain-related changes brought on by pregnancy; identify different types of cognition and memory that may be affected by pregnancy; and anticipate questions and appropriately counsel pregnant patients about concerns regarding cognitive changes.